Interacción de hormonas vegetales utilizadas en la fase de establecimiento in vitro en explantes de piña ananas comosus l híbrido md-2 - Ajila Celi, Gabriela Eugenia (2014)
The research was conducted in the laboratory of Plant Biotechnology, Faculty of Agricultural Sciences at the Technical University of Machala in Santa Ines worked farm in conducting experimental work on the in vitro propagation of pineapple from son and pacifiers using hormones IAA and BAP as endpoint of the trial. The objectives were: 1. Determine the optimal concentrations of two Indo Phyto regulators acetic acid (IAA) and benzylaminopurine (BAP) on Murashige and Skoog (MS) solid to the initiation phase; 2.Establish the optimum explant hybrid pineapple MD-2. Autoclave materials from the in vitro multiplication technique, including Sodium EDTA, Myo-inositol, thiamine, Sugar, Agar, IAA and BAP were used, and. The genetic material, the hybrid offspring pineapple MD-2 was obtained at the ranch "COCHA" located in Valle Hermoso Km 25 way Quininde. Treatments consisted of two types of explants of "children" and "suckers" two hormones, IAA (indole acetic acid), BAP (Benzyl amino purine) at doses 0.5 and 1.0 mg / l of medium, invitro propagation, 10 treatments, 8 corresponded to 4 arrangements of the two hormones and two types of explants as absolute controls. The variables were: number of leaf primordia. Percentage of contamination and survival. The material, kids and suckers were immersed for 6 hours Benlate suspensions, then cut them up to 6 cm long. Explants 2 x 2 cm around the yolk. These were washed with water more antioxidant Cysteine 30 mg / liter. The explants were disinfected in a laminar flow chamber with alcohol and phenol, sodium hypochlorite. Explants final 1 x 1 cm, with apex and corm, which units were seeded propagation. A solid medium was used with different concentrations for each treatment, the medium was adjusted to a pH of 5.8, with a temperature of 25 ± 2 ° C, with a light intensity of 1000 light and photoperiod of 14 ± 2 hours. Treatments were analyzed by one-way ANOVA and linear regression technique to obtain estimates of the rates of formation of leaf primordia. Selection of explants children or pacifiers as regards the effect on the formation of leaf primordia gave differences in relative terms from 39% in favor of the explants taken from "children." Mixture of IAA and BAP phyto hormones combining 1.0-0.5 mg / l BAP IAA and was the most convenient in the assay conditions. The trend of emission primordia growth and survival was adjusted to a linear model, even for a discrete variable. The higher survival of explants from both son and pacifiers was achieved on treatment with IAA-BAP (1.0-0.5 mg / l) and contaminations of the explants in the laboratory were medium to high.